Current Rectification, Resistive Switching, and Stable NDR Effect in BaTiO3/CeO2 Heterostructure Devices. (9th May 2021) - Rehman, Shania; Kim, Honggyun; Patil, Harshada; Kadam, Kalyani D.; Sagar, Rizwan Ur Rehman; Aziz, Jamal; Um, Doo‐Seung; Khan, Muhammad Farooq; Kim, Deok‐kee
Abstract: Electronic devices with simultaneous manifestation of multiphysical properties are of great interest due to their possible application in multifunctional devices. In the present study, simultaneous execution of negative differential resistance (NDR) effect, current rectification (≈10 5 ), and resistive switching characteristics (≈10 3 ) are demonstrated in BaTiO3 /CeO2 heterostructure. Although the negative differential effect has gained huge attention, its instability and poor reproducibility at room temperature are the main obstacles to its possible application in electronic devices. However, in this report, the NDR is observed even after hundreds of cycles in BaTiO3 /CeO2 heterostructure at 300 K. For a detailed analysis of the NDR effect, AC conductance spectroscopy is performed, which reveals that the presence of NDR is associated with trapping/detrapping of charge carriers at interface states formed at the BaTiO3 /CeO2 interface. In addition, the resistive switching and rectification effect are demonstrated due to a barrier at the BaTiO3 /CeO2 interface, which can be strongly modulated by thickness (20, 50, and 80 nm) based ferroelectric polarization of BaTiO3 . However, the results show that the remarkable performance of these devices makes them a potential candidate for application in multifunctional devices. Abstract : The simultaneous existence of negative differential resistance (NDR), current rectification, and resistive switching properties are revealed in BaTiO3 /CeO2 heterostructures. A stable NDR is found at 300 K which is attributed to trapping/detrapping of carriers at the BaTiO3 /CeO2 interface. Resistive switching and rectification are established due to the barrier at the BaTiO3 /CeO2 junction which is strongly modulated by thickness‐based ferroelectric polarization of BaTiO3 .